Extrusion Shear Printing: Automatic Transformation of Membrane‐Type Electronic Devices into Complex 3D Structures via Extrusion Shear Printing and Thermal Relaxation of Acrylonitrile–Butadiene–Styrene Frameworks (Adv. Funct. Mater. 5/2020). (29th January 2020) - Jang, Hun Soo; Yoo, Seonggwang; Kang, Seong Hyeon; Park, Jongjun; Kim, Gi‐Gwan; Ko, Heung Cho
Abstract : In article number 1907384, Heung Cho Ko and co‐workers demonstrate a novel technology for automatic shape transformation of electronic devices from 2D to 3D via extrusion shear printing and thermal relaxation of acrylonitrile–butadiene–styrene (ABS) frameworks. The transition from the glassy to rubbery state and reflow of the ABS polymer chains provide mechanical and electrical stability of electronic devices during transformation to develop complex 3D forms.